What is the State of the Stone Analysis Techniques in Urolithiasis? - Basiri, Abbas; Taheri, Maryam; Taheri, Fatemeh (Urology Journal, 2012)
PURPOSE: To compare and evaluate the mostly used methods of urinary stone analysis. MATERIALS AND METHODS: We searched PubMed and Google Scholar for “urolithiasis, nephrolithiasis, renal stone, and kidney stone” combined with “stone analysis, spectroscopy, X-ray diffraction, chemical analysis, mass spectrometry, and laser-induced breakdown spectroscopy, review article, and quality control assessment.” RESULTS: We identified 24 articles about reviews of the principles of stone analysis techniques and their quality control trials. Seven articles were not in English language; hence, were omitted from this review. The remaining 17 articles and their related references were studied thoroughly. There are various chemical and physical techniques available for urinary stone analysis. The correct stone analysis has to identify not only all stone components, but also the molecular structure and crystalline forms of them with the exact quantitative determination of each component. CONCLUSION: The knowledge of urinary stone composition is important for understanding pathophysiology, choice of treatment modality, and prevention of recurrences of urolithiasis, but up to now, a standard method has not been defined. Although there are many techniques available for identifying the urinary stone composition and structure, no single method can provide all the requiring information. Therefore, a combination of structural and morphological tests is needed for this purpose.